Scaphoid Fracture Non Union Treated by Bone Graft and Plaster of Paris Cast Splint. - Majeed, Ghadeer H.; Al- Iedani, Mohammed S. (AL-Kindy College Medical Journal, 2012)
Objective: to evaluate the results of (Modification of Russe method) in treatment of nonunion fracture scaphoid bone by bone graft with external splintage (plaster of paris cast (pop ). Methods:Prospective study done on 26 patients (24 male, 2 female), age range between 25-42 years (mean age 34 years), fracture site at middle 1/3 with minimal displacements with no carpal bone or radial bone injury, technique of Matte- Russe method (explore the bone through volar approach using bone graft from iliac crest (cortico-cancellous peg plus cancellus bone) with thumb spica for 90 days with period of follow up 12-18 months. Results: out of 26 patients treated by this method , 23 patients (88.5%) union was achieved radiologically by the end of 3rd month &progressed over the next 3 months, range of motion of the wrist & power of grip increased gradually became almost comparable to the normal side by the end of sixth month , 5-7 degrees loss of dorsiflexion was residual in 6 patients . Three patients (11.5%) did not show union radiolgically after sixth postoperative month, their local symptoms were better than before surgery ,they were not keen to have another operation .No complications were noticed, wound healed well ,patient tolerance was good Conclusion: the use of cancellous bone graft with plaster of paris (p.o.p.) splint is less demanding surgically& less coasty and resulted in good results(88.5% healed well ).we recommend this treatment as a method for treating nonunion of carpal scaphoid bone